Outcome of Early Laparoscopic Cholecystectomy in Acute Calculus Cholecystitis (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: : The surgical management of patients presenting with acute calculus cholecystitis remains controversial.Objective: The aim of this study was to evaluate the safety and feasibility of early laparoscopic cholecystectomy for acute calculus cholecystitis and to document the outcome of early laparoscopic cholecystectomy.Methodology: This observational comparative study was carried out in the Department of General Surgery of Sylhet MAG Osmani Medical College Hospital, Sylhet from July 2006 to June 2008, a period of 24 months. The study group enrolled 101 patients of both sexes who underwent laparoscopic cholecystectomy surgery and divided into two groups. 51 patients with a diagnosis of acute calculus cholecystitis were assigned randomly to early laparoscopic cholecystectomy within 72 h of admission (early group, n=51) or to initial conservative treatment followed by elective laparoscopic cholecystectomy, 6 to 12 weeks later (elective group, n=50).Results: There was no significant difference in operation times (early, 81.98 vs elective, 79.96), conversion rates (early, 5.88% vs elective 10%) or postoperative complications (early 31,4% vs elective,24%).However, during early laparoscopic cholecystectomy distended gallbladder containing infected bile was more in 41 patients (80.01%) while 04 patients (09%) and 03 patients (7.20%) in elective laparoscopic cholecystectomy (p>0.05) and significantly (p